К вопросу о соотносительности словообразовательных элементов в русском языке - Динь Зиап (H. : ĐHQGHN, 2017)
When looking at the word-forming components in Russian, traditional approach often takes stems as the starting point. On the basis of this approach, the author of this article thinks that when looking at the problem of word formation, it is necessary to look at the internal structure of the word-forming components (internally oriented approach) on the one hand, and their correlations with other words in the lexical system of Russian (externally oriented approach) on the other. Following this approach, the author offers some suggestions on the correlations between the root morphemes and the affixational morphemes in Russian. It is hoped that the article will make a contribution to the study of Russian vocabulary in general and to the study of word formation in particular.